Desenvolvimento de liderança para enfermeiros da saúde da família com o uso da estratégia coaching em grupo - Rocha, Bárbara Souza (2014)
The Family Health Strategy, reorienting considered practices in health care model, in its complexity brings an action that emphasizes teamwork, participation and social mobilization, professional autonomy and complementarity of practice and care management. In this context, the nurse has been recognized as a professional who works in leadership at all levels of management. Aware of the presence of weaknesses in academic training to develop skills essential to this task and the lack of investment in improvement programs that emphasize this theme, we aimed to analyze and implement a process of leadership development for nurses using the Family Health coaching group as a guiding tool. Action research was methodological option in the conduct of research by enabling the interaction between researcher and participants at the time of production of the survey results and focus on the change of the reality. We opted for the intervention group by enabling the exchange and learning through living with others, and the use of coaching, for goals to give the change process, defining steps. Following phases of coaching, nurses experienced the stage of the evaluation, which built a picture of the current situation experienced in leadership, pointing out difficulties in professional identity and occupation of spaces in this sphere of activity. In the grounds of personal issues and how these characteristics influence the leadership and in the formulation, the group was led to develop their leadership skills, particularly communication, feedback, and the act of delegating were discussed. Implementation concept, skills and attitudes for good leadership practices, as well as potential resources for their development have been deepened. The phase transformation nurses pointed out the changes made after the intervention and consolidation, there was strengthening of experienced change and identifying the effects of the intervention. We conclude that the qualification should focus more meaningful learning practices involving participants in the change process. Likewise, it is necessary to use innovative tools to deepen their understanding of themselves and the situation through experimentation and experience, aiming to change attitudes and behaviors in managerial practice.